2022
DOI: 10.1136/bmjopen-2021-058060
|View full text |Cite|
|
Sign up to set email alerts
|

Who is engaging with lateral flow testing for COVID-19 in the UK? The COVID-19 Rapid Survey of Adherence to Interventions and Responses (CORSAIR) study

Abstract: ObjectivesTo investigate uptake of lateral flow testing, reporting of test results and psychological, contextual and socio-demographic factors associated with testing.DesignA series of four fortnightly online cross-sectional surveys.SettingData collected from 19 April 2021 to 2 June 2021.ParticipantsPeople living in England and Scotland, aged 18 years or over, excluding those who reported their most recent test was a polymerase chain reaction (PCR) test (n=6646, n≈1600 per survey).Main outcome measuresHaving c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 26 publications
3
19
0
Order By: Relevance
“…We have previously shown that use of a test is more common in employees who work for specific sectors where daily LFTs are the norm. 13 It may be that taking a test is a marker of working in a sector where tackling the spread of infectious disease is viewed as a priority. It may also be that using tests indicates adherence to government advice in general.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that use of a test is more common in employees who work for specific sectors where daily LFTs are the norm. 13 It may be that taking a test is a marker of working in a sector where tackling the spread of infectious disease is viewed as a priority. It may also be that using tests indicates adherence to government advice in general.…”
Section: Discussionmentioning
confidence: 99%
“…In the UK, large studies have found that compliance with NPIs was generally high and sustained throughout the duration of the first two years when legal measures were in place (Fancourt et al 2022). However, other research suggests that adherence to specific behaviours, for example home-testing and self-isolation may have relatively low at various points during the pandemic (Rubin et al 2022;Smith et al 2022). Our qualitative research earlier in the pandemic revealed that whilst people reported high self-adherence to COVID-19 guidance and rules, they perceived there to be low adherence in others (Williams et al 2020;.…”
Section: Introductionmentioning
confidence: 58%
“…This work was undertaken in a region with a high number of cases and therefore young people may have been more concerned about infecting others, compared with places where the incidence was lower. Previous research has highlighted that concern about COVID-19 and the impact to self and others contributed to willingness to test,20 as well as adherence to other public health measures such as self-isolation 4…”
Section: Discussionmentioning
confidence: 99%
“…With LFTs, results were provided on the test kit within 30 min of taking a test. Results should have been registered with an official government agency, for example, GOV.UK or NHS Test and Trace, however research suggests this was not done routinely 4…”
Section: Introductionmentioning
confidence: 99%